Implementation of Child-Friendly School: Analytical Study - Athi Aliyatus Sya’ni; Harni Harni; Nurkolis Nurkolis (Lembaran Ilmu Kependidikan, 2025)
Background - Education is a conscious effort to develop the potential of students optimally. The purpose of education is to create someone who is qualified and has character so that they have a broad view of the future to achieve an ideal that is expected and are able to adapt quickly and appropriately in various environments. Purpose - The purpose of this research is to describe the implementation of child-friendly school (SRA) at SMK Negeri 1 Petarukan has attempted to fulfill the components of SRA, namely the SRA policy as a form of commitment to realizing SRA, the implementation of a child-friendly and enjoyable learning process so as to minimize the occurrence of violence and discrimination, child-friendly and non-dangerous facilities and infrastructure, participation of children, parents, community organizations, and the business world in the implementation of SRA at SMK Negeri 1 Petarukan. Method/approach - This mini research was conducted using a descriptive qualitative approach with a case study design. Data collection was carried out through observation, interviews and documents studies at SMK Negeri 1 Petarukan related to the implementation of child-friendly school. Findings - Based on data and finding from SMK Negeri 1 Petarukan, the following is a discussion about the implementation of child-friendly school at SMK Negeri 1 Petaruka. There are six components developed in child-friendly school. The six components are: (1) Child-friendly school policies; (2) Education and education personnel trained in children's rights; (3) Implementation of a child-friendly learning process; (4) Child-friendly school facilities and infrastructure; (5) Child participation; (6) Participation of parent, alumni, community institutions and the business world. Conclusions – This research proposes innovations teaching methods and school environments that create safe, comfortable and enjoyable learning atmosphere for all students, including those with special needs. Novelty/Originality/Value - Conclusions - The novelty of the Child-Friendly School (SRA) research on the teaching and learning process that emphasizes the fulfillment of children's rights, justice and protection from violence in schools.